Single-Stage Craniectomy and Cranioplasty for Multilobular Osteochondrosarcoma Managed with a Custom Additive Manufactured Titanium Plate in a Dog. (2nd December 2019) - Hayes, Galina M.; Demeter, Elena A.; Choi, Eunju; Oblak, Michelle
Abstract : A 9-year-old spayed female dachshund presented with a large multilobular osteochondrosarcoma of the crania, with obliteration of approximately 70% of the surface area of the dorsal calvaria and intracranial extension. The mass was excised with histologically clean lateral bone margins (2–4 mm) and invasion at the deep margin. The resulting defect was reconstructed with a custom titanium plate. The patient recovered routinely and was asymptomatic until 7 months postoperatively. The patient developed intractable seizures 7 months postoperatively and was euthanized. Post-mortem examination showed tumor regrowth within the brain parenchyma. No abnormalities were seen associated with the plate. The patient-specific, custom additive manufactured titanium plate provided an excellent option for anatomic reconstruction and protection of the brain over a relatively large area with no complications noted.